Имущественное положение граждан в трансформирующемся обществе - Чапская, И. (Социология: теория, методы, маркетинг, 1999)
The discussion of a stratification model of modern Ukrainian society, as well as, the reference of individual or family to specific social group is based on sociological studies of material life surrounding. Comparative analysis of sociologic data on property position of residents of Odessa oblast has allowed the author to conclude that personal property, being an importantfactor of society structural development, influences the social well-being and social adaptation under the new conditions.